Larvicidal effects of murraya koenigii extracts against the larvae of metisa plana / Noorshilawati Abdul Aziz, Nur Suraya Abdullah and Norhana Abdullah - Abdul Aziz, Noorshilawati; Abdullah, Nur Suraya; Abdullah, Norhana (Universiti Teknologi MARA Cawangan Pahang, 2018)
Metisa plana is the most destructive pest in oil palm plantation area in Malaysia. It is a vigorous insect which feeding on the oil palm leaves. In Peninsular Malaysia, infestation of M. planawas estimated at about 4,904 ha. Its infestation has caused 33-40% yield losses. In this study, Murraya koenigii was chosen to evaluate the larvicidal activity against larvae of M. plana. The leaves immersed with different extracts at different concentration (50, 100, 200, 300, 400 and 500ppm) were provided as food source. The mortality rate was recorded every 6 hours for 3 days. The result revealed that all concentrations were effective to control the larvae. Hexane extracts which contains glycoside, terpenoid, phenol, alkaloid and tannin exhibited good potential as larvicidal as it demonstrated 100% mortality rate in the first 12 hours followed by chloroform extract which showed 100% mortality rate after 24 hours. Meanwhile, methanol leaves extracts at 50 ppm did not show any larvicidal activity against M. plana. However, M. koenigii aqueous leaves extract at 500 ppm recorded only 37% mortality rate after 36 hours. The results suggested that M. koenigii has potential for development as commercial insecticide for controlling M. plana due to its larvicidal effect